FOREIGN POLICY IN HYBRID WARFARE ENVIRONMENT – WAY FORWARD FOR PAKISTAN - Imtiaz Hussain Naz (Margalla Papers, 2021)
Hybrid warfare is neither a novel idea nor a new phenomenon. It has been evolving for ages, yet its manifestation in the contemporary era has intensified. Taking advantage of politico-ethnic fault lines, socio-religious vulnerabilities, and identity conflicts, hybrid warfare advocates using all means available including regular or irregular and conventional or unconventional ways of warfare to subdue the will of an adversary. An externally motivated and supported threat requires essential measures in the foreign policy domain to thwart and foil it outside the borders. Therefore, this paper deals with the conceptual aspects of hybrid warfare and highlights the contours of the hybrid threat currently confronting Pakistan. It navigates through the challenges for foreign policy formulation and implementation in a hybrid warfare environment and identifies loopholes and grey areas while recommending tangible measures.